Two new species of Isotopenola from a suburb of Melbourne, Australia (Collembola, Isotomidae) - Zhang, Yating; Yu, Daoyuan (Zootaxa, 2026)
To date, the genus Isotopenola Potapov, Babenko, Fjellberg & Greenslade comprises only five known species. In the present paper, two new species, i.e., Isotopenola chowni sp. nov. and Isotopenola hallasae sp. nov., are described from Endeavour Hills, Melbourne, Australia. Isotopenola chowni sp. nov. has a markedly large and variable number of tergal sensilla. It is similar to Isotopenola loftyensis (Womersley), but can be distinguished from the latter mainly by having equal sized ocelli and less chaetae on Ant. I and tibiotarsi. Isotopenola hallasae sp. nov. has a moderate number of tergal sensilla. It is similar to I. perterrens Greenslade & Potapov, but can be distinguished from the latter mainly by having less chaetae on Ant. I, tibiotarsi, and dens. A key to all species of Isotopenola is provided.